OpenStudy (anonymous):

(x-9/7)(x+7/9)

5 years ago
OpenStudy (anonymous):

x^2-16/63 thats as far as i have gotten

5 years ago
OpenStudy (dumbcow):

whats (-9/7)(7/9) ?

5 years ago
OpenStudy (anonymous):

x^2+(7/9-9/7)x-(-9/7)(7/9) =x^2 - (32/63)x - 1

5 years ago
OpenStudy (anonymous):

Here is the method I was taught to expand brackets

5 years ago
OpenStudy (anonymous):

\[(x-\frac{9}{7})(x+\frac{7}{9})=x^2+\frac{7x}{9}-\frac{9x}{7}-\frac{9*7}{7*9}\] \[=x^2+\frac{49x}{63}-\frac{81x}{63}-1\] \[=x^2-\frac{32x}{63}-1\]

5 years ago